2017
DOI: 10.18805/ijar.b-3401
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses in pigs on antioxidant supplementation during summer and winter

Abstract: The objective of the study was to assess the variability in the physiological responses of growing pigs on melatonin and vitamin E supplementation during summer and winter seasons.36 nos. of weaned crossbred (Hampshire X Assam local) female pigs were selected for the study. Eighteen (18) animals were subjected to treatment separately during summer and winter. The selected animals were divided into three groups, with six pigs in each group, consisting of the control group (Treatment 1), a second group comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Regulation of body temperature is one of the most essential mechanisms to maintain the homeostasis of the whole organism and to assist in disease diagnosis and health monitoring (Yazgan, 2017;Zhang et al, 2019). Biological functions often depend on body temperature which is closely associated with its surrounding ambient environment as well as behavior, performance and physiological parameters of pig (Kessel et al, 2010;Bertoldo et al, 2012;Chakraborty et al, 2018). Kessel et al (2010) noted that the rate of metabolic processes increases with temperature, however if temperature is elevated beyond a certain threshold limit, biological functions may not work properly.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of body temperature is one of the most essential mechanisms to maintain the homeostasis of the whole organism and to assist in disease diagnosis and health monitoring (Yazgan, 2017;Zhang et al, 2019). Biological functions often depend on body temperature which is closely associated with its surrounding ambient environment as well as behavior, performance and physiological parameters of pig (Kessel et al, 2010;Bertoldo et al, 2012;Chakraborty et al, 2018). Kessel et al (2010) noted that the rate of metabolic processes increases with temperature, however if temperature is elevated beyond a certain threshold limit, biological functions may not work properly.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is also in accordance with that of Mou et al (2018), where they reported that supplementation with methyl donors increased the antioxidant capacity of sows as well as newborn piglets by increasing the activities of catalase and glutathione peroxidase. In another study, supplementation of antioxidant improved the antioxidant status and the ability of pigs to combat stress (Chakraborty et al, 2018). Homocysteine (Hcy) concentrations in pigs are typically several folds higher than in other species, which results in increased levels of ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental indices . Thermal stress is generated by a combination of environmental factors, such as humidity and ambient temperature, and the anatomical fact that pigs have a decreased perspiration capacity [ 6 , 45 , 70 72 ]. Therefore, environmental indices and mathematical models have been developed to estimate the impact of the rise in environmental temperature on the thermal status of animals [ 43 46 , 64 , 65 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of increased respiratory frequency provides contactless method for monitoring the thermal state of the animal, as an increased respiratory rate is part of the adaptation strategy of an organism to cope with high temperature conditions to maintain thermoregulation, speeding up cooling through evaporative heat loss [ 95 , 103 ]. Pigs, in particular, must dissipate heat through perspiration, as they are deficient in sweat glands [ 72 , 78 , 95 , 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%